Association of Diabetes Mellitus with Carotid Artery Stenosis Undergoing Coronary Artery Bypass Graft in Bangladesh: A Prospective Cross-Sectional Study - Chowdhury MAT; Joshi D; Magdum M; Adhikary D; Saklayen S; Alauddin M; Ranjan R; Adhikary AB (International Journal of General Medicine)
Md Abir Tazim Chowdhury,1 Dharmendra Joshi,2 Munama Magdum,3 Dipannita Adhikary,4 SMG Saklayen,5 Md Alauddin,6 Redoy Ranjan,4,6 Asit Baran Adhikary7 1Department of Cardiothoracic and Vascular Surgery, Evercare Hospital Dhaka, Dhaka, Bangladesh; 2Department of Cardiac Surgery, Shahid Gangalal National Heart Centre, Kathmandu, Nepal; 3Department of Preventive and Social Medicine, National Institute of Preventive and Social Medicine, Dhaka, Bangladesh; 4Department of Biological Sciences, Royal Holloway University of London, London, UK; 5Department of Vascular Surgery, Ibrahim Cardiac Hospital & Research Institute, Dhaka, Bangladesh; 6Department of Cardiac Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh; 7Department of Cardiac Surgery, Impulse Hospital, Dhaka, BangladeshCorrespondence: Md Abir Tazim Chowdhury, Department of Cardiothoracic and Vascular Surgery, Evercare Hospital Dhaka, Dhaka, Bangladesh, Tel +8801718123463, Email chowdhuryabir0@gmail.comBackground: Atherosclerosis is a systemic vascular disease commonly affecting coronary and carotid arteries, particularly in diabetes mellitus (DM). This study assessed the association of DM with significant carotid artery stenosis (CAS) among the coronary artery disease (CAD) population undergoing isolated elective coronary artery bypass graft (CABG) surgery.Methods: A prospective cross-sectional study evaluated 100 Bangladeshi CAD patients who underwent isolated elective CABG from January 2017 to September 2019. Initially, a univariate analysis curtails the risk patterns, followed by a Pearson correlation analysis of significant CAS and glycated haemoglobin (HbA1c).Results: Although the majority of patients were male, females were higher in the diabetic than non-diabetic group (38.1% vs 15.5%; p=0.01). Overall, ~38% of diabetic patients had significantly higher ≥ 50% CAS. Further, 28.6% and 9.5% of the diabetic sample had 50– 70% and > 70% CAS, respectively, which is significantly (p =0.02) higher than the non-diabetic sample (8.6% and 1.7%, respectively). Additionally, diabetes was significantly more associated with both unilateral (31.0% vs 22.4%) and bilateral (45.2% vs 22.4%) CAS than the non-diabetic population (p=0.006). The Pearson correlation coefficient shows a significant positive association between higher glycated haemoglobin levels and > 50% CAS (correlation coefficient 0.270; p = 0.007).Conclusion: We found higher HbA1c had a significant positive correlation with > 50% CAS in diabetic patients undergoing elective CABG, recommending preoperative carotid screening, especially elderly individuals.Keywords: carotid artery stenosis, coronary artery disease, diabetes mellitus, duplex scan